Phsycological Effects of Sports Injuries - A. Ramírez; R. Alzate; I. Lázaro (Asociación Española de Ciencias del Deporte, 2010)
The continued practice of physical activity and sport, has been related with better moods and self-efficiency. This study analyses the consequences on mood disturbance and perception of physical ability that result from an interruption in training as a result of an injury. Significant differences were found in these dependent variables between the injured and non-injured athletes. A significant correlation was also found between self-efficiency and anger at the onset of injury. KEY WORDS: Sport, Injury, Self Efficiency, Mood State